Isolation and identification of Enteropathogenic Escherichia coli (EPEC) in paediatric diarrhoeal patients by detection of bfpA gene by PCR (Bangladesh Journal of Medical Microbiology, 2013)
This study has been undertaken to investigate the isolation and identification of EPEC strains from paediatric diarrhoeal patients.Total 300 samples were studied.Two hundred and seventy two samples from patients with diarrhoea and  28 samples from control children were collected from two tertiary care hospital. Esch. coli was isolated and identified from all the 300 samples including patient and control using standard microbiological techniques. EPEC strains were identified on the basis of  presence of bundle forming pilus (bfpA) gene. Out of 272 samples from diarrhoeal patient only Esch. coli was isolated from 240 (88.2%) samples. Shigella spp. with Esch. coli were isolated from 27 (10%) specimens and Salmonella spp. with Esch. coli were isolated from 5 (1.8%) samples. Among 272 samples 20 (7.35%) isolates were identified as EPEC on the basis of presence of bfpA gene detected by polymerase chain reaction. EPEC strains were identified from those 240 samples, from which Esch. coli had been isolated only. No EPEC strain was identified  from control children. Rapid and reliable detection of EPEC is required for successful microbiological surveillance and for treatment of EPEC mediated diarrhoeal disease. bfpA gene detection by polymerase chain reaction can be a appropriate method where facilities for polymerase chain reaction are available.DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19324 Bangladesh J Med Microbiol 2013; 07(02): 2-5